2009
DOI: 10.1007/s10483-009-0312-y
|View full text |Cite
|
Sign up to set email alerts
|

Existence and joint continuity of local time of multi-parameter fractional Lévy processes

Abstract: In this paper, we introduce the definition of a multi-parameter fractional Lévy process and its local time, and show its decomposition. Using the decomposition, we prove existence and joint continuity of its local time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this section, we briefly recall the definition and properties of FLP. More studies on the FLP can be found in Benassi et al (2002), Bender et al (2012), Engelke (2013), Fink et al (2011), Lacaux (2004, Lin et al (2009), Tikanmäki et al (2011) and the references therein.…”
Section: Preliminariesmentioning
confidence: 99%
“…In this section, we briefly recall the definition and properties of FLP. More studies on the FLP can be found in Benassi et al (2002), Bender et al (2012), Engelke (2013), Fink et al (2011), Lacaux (2004, Lin et al (2009), Tikanmäki et al (2011) and the references therein.…”
Section: Preliminariesmentioning
confidence: 99%
“…For the study of fLp see Bender et al. [3], Fink and Klüppelberg [7], Lin and Cheng [18], Benassi et al. [1], Lacaux [16], Engelke [6] and the references therein.…”
Section: Introductionmentioning
confidence: 99%